Sistem Kerja Survei Kepuasan Masyarakat Kantor Camat Tanjung Tiram Kabupaten Batu Bara - Elsa Rahmadani (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
This research aims to analyze and develop a community satisfaction survey work system carried out by the Tanjung Tiram District Head Office, Batu Bara Regency. Community satisfaction surveys are one way to measure the extent to which public services provided by government agencies, in this case the sub-district office, meet the needs and expectations of the community. This research includes the design, implementation, and evaluation of the system used to collect and analyze survey data. Through representative and systematic data collection, it is hoped that the survey results can provide constructive input for improving the quality of public services in the region. It is hoped that the results of this research can provide useful recommendations for policy makers in optimizing the public service system based on community satisfaction in Batu Bara Regency